(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article describes nozogeographical research, which is the main direction of medical geography, the combination and interaction of ecological-climatic, socio-economic, socio-biological, medical and organizational factors affecting the aggravation of the nozogeographical situation, as well as the medical-geographical factors that determine the health status of the population.